Drying characteristics and quality of bananas under infrared radiation heating - Pekke, Milly A.; Pan, Zhongli; Atungulu, Griffiths G.; Smith, Gary; Thompson, James F. (International Journal of Agricultural and Biological Engineering, 2013)
Hot air (HA) drying of banana has low drying efficiency and results in undesirable product quality. The objectives of this research were to investigate the feasibility of infrared (IR) heating to improve banana drying rate, evaluate quality of the dried product, and establish models for predicting drying characteristics. Banana slices of 5 mm and 8 mm thickness were dried with IR and HA at product temperatures of 60C, 70C and 80C. Banana drying characteristics and changes in residual polyphenol oxidase (PPO), Hydroxymethylfurfural (HMF), color, moisture content (MC) and water activity during the treatments were investigated. Results showed that significant moisture reduction and higher drying rates were achieved with IR drying compared to HA drying in the early stage. The drying data could be fitted to the Page model for accurate prediction of MC change for IR and HA drying with mean R2 of 0.983. It was noted that enzyme inactivation occurred more quickly with IR than with HA drying. A unique response of PPO under IR and HA drying was revealed. IR heating of banana inactivated PPO within the first 20 min of drying at 60C, 70C and 80C, while PPO was first activated before inactivation at 60C and 70C drying with HA. The highest HMF content occurred in banana slices with 5 mm thickness dried with IR at a product temperature of 80C. It is therefore recommendable to dry banana with IR at product temperature of 70C or below to preserve the product quality. These findings are new and provide more insight in the application of IR heating for drying banana for improved drying rate and product quality.